A Case Report of Suicide with Chloroquine Overdose and Review of Literature - Maryam Hosseini; Reza Khoshnoud; Saeed Gholamzadeh; Gholamreza Naseri; Tahereh Tarian; Abdorrasoul Malekpour; Mohammad Zarenejad (Fasa University of Medical Sciences, 2016)
Background & Objective: Suicide is considered as the tenth cause of death worldwide. There are several suicide reports consist in the use of certain unusual drugs, such as chloroquine. Case report: The cadaver of a 25-year-old single woman was found dead in her home and with suspect to using toxins or drugs was brought to Fars Province Forensic administration. She had history of psychiatric problems for which had referred to psychologist several times. Results: After the autopsy, there was no observation of pathologic lesions in her samples of liver, kidney, or heart. In bile samples, using Thin Layer Chromatography (TLC) and High Performance Liquid Chromatography (HPLC) methods, chloroquine was detected. In visceral and gut samples, chloroquine was found using TLC as +4 reactions and it was confirmed by HPLC and Gas Chromatography Mass Spectrometry (GC-MS). After examining all the aspects, eventually chloroquine overdose and its complications was determined as the cause of the death. Conclusion: Due to the high incidence of suicide in depressed patients and according to family and previous positive experience, preventive strategies based on the recognition and the treatment of depressed patients and also teaching the families to diagnose the illness in addition to the limitation of the free access to chloroquine and similar drugs is suggested to reduce overdose complications or suicide.